Studying film with André Bazin (2019)
This book is not so much a study on André Bazin as it is a study with him on film. Deceased in 1958 at the age of forty, his ideas and theories have been praised, criticized, defended and appropriated to the point where much scholarship on him is either antagonistic or apologetic. Whereas the following pages are invested in testing the relevance of his work for contemporary film and media studies, I do not aim to defend nor appropriate Bazin. Instead, I wish to make his criticism (the metaphors, the references, the paradoxes) reverberate with contemporary perspectives and thereby extend the potential of his lineage today. Studying film… Bazin’s time as a f ilm critic in the 1940s and 1950s, spanning from the Nazi occupation of France into the post-war era in which film culture started to flourish in Paris, was marked not only by the gradual institutionalization of film studies at universities but also by the emergence of the first comprehensive film history books. Established at the Sorbonne right after the Second World War, the Filmology movement can be said to have initiated the ‘serious’ study of cinema, leaning on academic methodologies that were anthropological, sociological, psychological or philosophical in nature. With their laboratories set up to perform cognitive and behavioural experiments; their books, lectures, and conferences on cinema; and – let’s not forget – a theater for screenings, the university embarked on a rigorous analysis of film. And, as the seventh art started to outgrow its critics, there was a real necessity to document its evolution in film histories. Bazin, though a passionate teacher and supportive of film books (historical or other), was not a film historian nor was he a scholar. As the other visionary French critic Serge Daney puts it, ‘Bazin, educator, would never become professor. He became more than that: an initiator’.1 … with Bazin. To him, education and cinema were inextricably linked, but rather than finding place in the sterile laboratories or lecture halls at the Sorbonne, his work was socially oriented. By the time of the Liberation, he had brought film clubs to factories, farming communities and literary as well as student societies, on a national and international level. Around 1945, along with the immense amount of written criticism he would produce for newspapers, weekly and monthly magazines, he became responsible for the film programs at Travail et culture, an organization involved in popular education.